VD_FINDINFO HC / 2015 / 943 vom 4. November 2015 - VD Tribunal cantonal (2015)
BAIL À LOYER, LOYER, DEMEURE, RÉSILIATION, EXPULSION DE LOCATAIRE, CAS CLAIR | 257d al. 1 CO, 257d al. 2 CO, 271 al. 1 CO, 257 CPC (CH)